1994
DOI: 10.1515/reveh.1994.10.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Response of Brain Electrical Activity (EEG) and Cerebral Circulation (REG) to Microwave Exposure in Rats

Abstract: The correlations between physiological modalities in microwave field-activated systemic or localized regulatory mechanisms with changes in the central nervous system (CNS) seem not to be identical. These problems are important because of the increased number of radiating appliances, e.g. portable radios and mobile telephones.In two series of experiments on anaesthetized rats (N=40) (i) before and after 10 min, whole body exposures to 2.45 GHz CW microwaves, and (ii) during 30 min exposures to 4 GHz amplitude m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 8 publications
2
18
0
1
Order By: Relevance
“…Whether the effects reported in these studies depend on the pres-' ence of the modulation is not known. Three studies (19,28,32) report effects with amplitude modulation but not with continuous radiation, and 4 studies report different effects with continuous and AM exposures (13,33,34,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether the effects reported in these studies depend on the pres-' ence of the modulation is not known. Three studies (19,28,32) report effects with amplitude modulation but not with continuous radiation, and 4 studies report different effects with continuous and AM exposures (13,33,34,43).…”
Section: Discussionmentioning
confidence: 99%
“…No effects of continuous-wave microwaves at 10 pW/cm2 were found on the total power of the electroencephalographic (EEG) spectrum from rats (34). However, an increase in the delta band and a decrease of the alpha and beta bands were observed after a 5-minute exposure to 2.45-GHz pulsed microwaves at 3 pW/cm2 (217 Hz, 118 duty cycle) (35).…”
Section: Effects Of Amplitude-modulated Radiofrequency Radiation In Vivomentioning
confidence: 99%
“…In acute experiments on rats, changes were seen in EEG and cerebral blood flow (CBF) upon MWexposure [Thuroczy et al, 1994]. A whole body exposure of 30 mW/cm 2 , 2.45 GHz continuous wave (CW) for 10 min caused an increase in the total power of the EEG Klitzing et al [1995] (Continued) Human studies.…”
Section: Electroencephalography and Evoked Responsesmentioning
confidence: 99%
“…A microdialysis study of amino acid release in the brain has been performed on anaesthetised animals exposed to microwave thermal stress, but at SAR of 40 W/kg [Mason et al, 1997] it showed increases of aspartic acid, serine and glycine release. Some other works using lower power density indicated a slight disturbance of EEG [Thuroczy et al, 1994;Reiser et al, 1995;Vorobyov et al, 1997;Freude et al, 1998] and sleep pattern [Mann and Röschke, 1996;Wagner et al, 1998]. …”
Section: Introductionmentioning
confidence: 98%